2004
DOI: 10.4025/actasciagron.v26i1.1968
|View full text |Cite
|
Sign up to set email alerts
|

Influência da remoção do meristema apical sobre os componentes de produtividade em populações de plantas de soja

Abstract: RESUMO.O trabalho teve por objetivo verificar a eficiência da remoção do meristema apical em diferentes populações de plantas de soja quanto ao estímulo à ramificação e verificar se a remoção do meristema contribui no aumento da produtividade e reduz os trabalhos de tutoramento, em condições de cultivo em casa-de-vegetação, com a variedade UFV-18 (Patos de Minas), na safra 2001/02. Os tratamentos foram constituídos de populações de plantas variando entre 1 e 6 por vaso, 3 alturas de remoção do meristema apical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Contrary to the observations of other researchers, greater branching occurred in the witness, or in the treatment that received cutting of only the cotyledons at VC stage (Barzan et al, 2016). The works found that plants with removal presented lower height, one of the possible justifications is the induction of secondary growth more quickly compared to plants without removal (Tancredi et al, 2004;Tancredi et al, 2006).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Contrary to the observations of other researchers, greater branching occurred in the witness, or in the treatment that received cutting of only the cotyledons at VC stage (Barzan et al, 2016). The works found that plants with removal presented lower height, one of the possible justifications is the induction of secondary growth more quickly compared to plants without removal (Tancredi et al, 2004;Tancredi et al, 2006).…”
Section: Resultsmentioning
confidence: 82%
“…The response for these traits was similar and the number of nodes of the main stem was also reduced as a result of reduced plant size (Tancredi et al, 2006). Removal of the apical meristem at 25, 50 and 75 cm was effective in reducing the masses, indicating less growth of these compared to the control (no cutting) (Tancredi, Sediyama, Reis, Cecon, & Teixeira, 2004).…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, it is necessary to develop strategies to increase the deposition of herbicide spray droplets on the lower part of the canopy. In this way, soybean cultivars with low height, branch number, and leaf area index exhibited more product deposition in the middle and lower canopy layers (30).…”
Section: Resultsmentioning
confidence: 92%
“…Artificial hybridization activities were performed in greenhouse of the Soybean Genetic CAVINESS, 1977), the apical meristem was removed, aiming to reduce the necessity of plant tutoring (TANCREDI et al, 2004). Subsequently, plants of the crossing block were grown according to culture recommendations (EMBRAPA, 2008).…”
Section: Methodsmentioning
confidence: 99%